2015
DOI: 10.1158/0008-5472.can-14-1693
|View full text |Cite
|
Sign up to set email alerts
|

Agr2 Mediates Paracrine Effects on Stromal Fibroblasts That Promote Invasion by Gastric Signet-Ring Carcinoma Cells

Abstract: Agr2 is a disulfide isomerase residing in the endoplasmic reticulum (ER), which physiologically regulates protein folding and mediates resistance to ER stress. Agr2 is overexpressed in adenocarcinomas of various organs, where it participates in neoplastic transformation and metastasis, therefore acts as a pro-oncogenic protein. Besides its normal localization in the ER, Agr2 is also found in the serum and urine of cancer patients, although the physiological significance of extracellular Agr2 is poorly understo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 40 publications
1
23
0
1
Order By: Relevance
“…and paracrine effect on the Fibro. to facilitate cell migration which is correlated with recent work published by Tsuji et al [30]. It is also important to note that externally applied AGR2 accelerated early activation of Fibro.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…and paracrine effect on the Fibro. to facilitate cell migration which is correlated with recent work published by Tsuji et al [30]. It is also important to note that externally applied AGR2 accelerated early activation of Fibro.…”
Section: Discussionsupporting
confidence: 85%
“…by regulating the formation of focal adhesions. These AGR2 functions in wound healing involve FAK and JNK signaling pathways and require AGR2 adhesion domain (amino acids [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. Our finding indicates that external AGR2 may represent an alternative strategy for the development of therapeutics for wounds with large exposure area or difficult-to-heal chronic wounds.…”
Section: Introductionmentioning
confidence: 97%
“…Cancer-secreted AGR2 could activate stromal fibroblasts (cancer-associated stromal cells vs . normal tissue stromal cells) to promote fibroblast associated cancer invasion of gastric cancer cells [19]. AGR2 could activate ER stress response genes [11], to stimulate cell proliferation of AGR2-negative pancreatic tumor cells, and to enhance drug resistance [10].…”
Section: Introductionmentioning
confidence: 99%
“…Lucia Sommerova et al described that loss of intracellular AGR2 in cell lines caused a variation from epithelial to mesenchymal phenotype and establishment of intracellular AGR2 expression launched EMT 43 . However, other studies suggested that extracellular AGR2 could interrupt adherens junctions, disrupt basal laminin and activate broblastassociated cancer invasion, promoting epithelial morphogenesis and tumorigenesis 44 . To date, no researches about correlation between AGR2 and ribosome biogenesis have been reported.…”
Section: Dicussionmentioning
confidence: 99%